2022
DOI: 10.3390/ijerph19116911
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Wellbeing among University Students and Recent Graduates: Evidence from the United Kingdom

Abstract: This study compares students’ and recent graduates’ perceptions of their subjective wellbeing and offers support mechanisms and resources to enhance wellbeing in higher education. Survey data were collected in September 2021 from 414 UK-based higher education students and recent graduates on their self-perceived subjective wellbeing in March 2020 (before COVID-19 regulations restrictions) and September 2021 (18 months later). Findings showed that subjective wellbeing scores fell for almost three-quarters of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 53 publications
(89 reference statements)
1
21
0
Order By: Relevance
“…The findings indicate that individuals now see a greater fit with employers who provide meaningful work opportunities and prioritise their health and well-being. This builds on previous research by Donald and Jackson (2022), whereby almost three-quarters of recent graduates reported a drop in self-perceived subjective well-being due to the pandemic. Participants of the study called on organisations to provide an environment where they could “learn” and “earn” concurrently by offering training opportunities, job crafting and salary and benefits progression.…”
Section: Discussionsupporting
confidence: 80%
“…The findings indicate that individuals now see a greater fit with employers who provide meaningful work opportunities and prioritise their health and well-being. This builds on previous research by Donald and Jackson (2022), whereby almost three-quarters of recent graduates reported a drop in self-perceived subjective well-being due to the pandemic. Participants of the study called on organisations to provide an environment where they could “learn” and “earn” concurrently by offering training opportunities, job crafting and salary and benefits progression.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, a study conducted in 2020 among Australian university students during the COVID-19 pandemic reported that 66.3% of students had poor wellbeing (Liu et al 2021). The differences in the level of well-being reported could be explained based on evidence that the COVID-19 pandemic has adversely influenced the well-being of young people especially students and graduates (Donald and Jackson 2022;Martínez 2020). As nursing students are facing everyday challenges while trying to cope with academic requirements and patient care, it is cardinal that we recognise the factors that might influence their well-being.…”
Section: Discussionmentioning
confidence: 99%
“…However, reduced opportunities for lifewide learning and a lack of understanding of the recruitment process mean some students receive many rejection decisions, leading to high stress levels and loss of confidence due to uncertainty for the future. These experiences can have a compound effect since three-quarters of university students, and recent graduates report reduced subjective well-being since the pandemic began (Donald & Jackson, 2022). Donald et al (2019) propose that the self-perceived employability of students increases when they develop human capital, seek career advice, and proactively take ownership of their careers.…”
Section: Challengesmentioning
confidence: 99%